LEVOSIMENDAN AS BRIDGING THERAPY IN ADVANCED HEART FAILURE: CURRENT STATE OF KNOWLEDGE AND CLINICAL PERSPECTIVES - Marcin Schulz; Michał Kulczak; Dawid Studziński; Anna Kołcz; Agnieszka Morawa; Karolina Osińska (International Journal of Innovative Technologies in Social Science, 2025)
Advanced heart failure (AHF) constitutes a terminal expression of cardiovascular disease, associated with severe, refractory symptoms and high mortality despite optimized medical therapy. Levosimendan, a first-in-class inodilator, addresses this challenge, acting as a calcium sensitizer and potassium channel opener. Its unique tripartite mechanism provides positive inotropy independently of the cAMP pathway, critically avoiding increased intracellular calcium or myocardial oxygen demand. The active metabolite, OR-1896, ensures prolonged hemodynamic benefits lasting up to two weeks, supporting intermittent, outpatient bridging strategies. This systematic literature review synthesized current evidence by applying a rigorous search strategy across biomedical databases, resulting in the inclusion of 32 scientific publications encompassing high-level evidence such as meta-analyses, randomized controlled trials (RCTs), and cohort studies. Pooled analyses suggest that repetitive levosimendan administration significantly improves Left Ventricular Ejection Fraction (LVEF), reduces NT-proBNP levels, and is associated with a reduced risk of all-cause mortality (RR 0.60). Furthermore, it confers vital organoprotective effects, notably improving renal function in patients awaiting heart transplantation (HTx), and its preoperative use as a "bridge to transplant" (BTT) is deemed safe. Despite compelling data from small RCTs (e.g., LION-HEART), the field requires larger, definitive studies—such as the ongoing LEIA-HF trial—to establish the precise role of levosimendan in contemporary AHF management.